Long-Term Therapy with the Guanine Nucleoside Analog Penciclovir Controls Chronic Duck Hepatitis B Virus Infection In Vivo - Lin, Enjarn (American Society for Microbiology, 1998)
Ducks congenitally infected with duck hepatitis B virus (DHBV) were treated with the antiviral guanine nucleoside analog penciclovir for 12 or 24 weeks at a dosage of 10 mg/kg of body weight per day. By the completion of both 12 and 24 weeks of therapy, molecular hybridization studies of the liver tissue revealed that the viral DNA, RNA, and protein levels were significantly reduced compared to those in the placebo-treated controls. Penciclovir treatment for 12 or 24 weeks was not associated with any toxicity, establishing the efficacy and safety of long-term penciclovir therapy in chronic DHBV infection.